Prototip Self Assessment Audit ISO 17799 - Pujianto Yugopuspito; Susanti Susanti; Sutrisno Sutrisno (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2007)
This paper presents a web-based application for a self assessment audit tool that is guided by ISO17799guidelines.The ISO17799 is a code of practice for information security management as part of the informationsecurity standard, and provides a set of controls and procedure to achieve security information. This selfassessment audit system shall indicate any security threats based on a pre-defined checklist, which is derivedfrom the implemented audit program of information technology as guided by the ISO17799. Current state of thisdevelopment is limited to Access Control, and System Development & Maintenance categories.Keywords: Web-based application, ISO 17799, IT Audit Program.